2014
DOI: 10.4161/15548627.2014.991665
|View full text |Cite|
|
Sign up to set email alerts
|

TSPO interacts with VDAC1 and triggers a ROS-mediated inhibition of mitochondrial quality control

Abstract: The 18-kDa TSPO (translocator protein) localizes on the outer mitochondrial membrane (OMM) and participates in cholesterol transport. Here, we report that TSPO inhibits mitochondrial autophagy downstream of the PINK1-PARK2 pathway, preventing essential ubiquitination of proteins. TSPO abolishes mitochondrial relocation of SQSTM1/p62 (sequestosome 1), and consequently that of the autophagic marker LC3 (microtubule-associated protein 1 light chain 3), thus leading to an accumulation of dysfunctional mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
189
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 85 publications
(86 reference statements)
6
189
1
1
Order By: Relevance
“…It has been suggested that TSPO could interact with VDAC1 or NOX2 to induce production of ROS (Gatliff et al 2014, Guilarte et al 2016. On the contrary, the association of TSPO with VDAC1 (Joo et al 2012, Joo et al 2015, or TSPO by itself (Guo et al 2015), could facilitate ROS neutralization.…”
Section: Tspo As An Enzyme For Protoporphyrin IX Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that TSPO could interact with VDAC1 or NOX2 to induce production of ROS (Gatliff et al 2014, Guilarte et al 2016. On the contrary, the association of TSPO with VDAC1 (Joo et al 2012, Joo et al 2015, or TSPO by itself (Guo et al 2015), could facilitate ROS neutralization.…”
Section: Tspo As An Enzyme For Protoporphyrin IX Degradationmentioning
confidence: 99%
“…Therefore, it is possible that these interpretations may be confounded with cellular effects associated with the obvious link between stress and ROS production. The TSPO-VDAC relationship to ROS production has had contrasting results in similar TSPO overexpression studies (Gatliff et al 2014, Joo et al 2012. The TSPO-NOX2 association (Guilarte et al 2016), remains a hypothesis.…”
Section: :1mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the ubiquitin ligase Mul1 also induces mitophagy by ubiquitinating mitofusin 2, required for mitochondrial fusion, which is consequently degraded increasing the rate of mitochondrial fission and mitophagy (Lokireddy et al, 2012). Conversely, negative regulation is achieved via deubiquitinases such as USP30 (Bingol et al, 2014) and the 18 kDa TSPO, which is upregulated during cellular stressaccumulates on mitochondria preventing autophagic clearance by limiting ubiquitination of OMM proteins (Gatliff et al, 2014). …”
Section: Molecular Physiology Of Mitochondrial Quality Controlmentioning
confidence: 99%
“…These findings clearly confirm that TSPO plays a key role in the antiproliferative activity of 1. Taking into consideration previously reported experimental evidence that TSPO affects energy homeostasis and that it is implicated in the control of mitochondrial ROS production, 11 we investigated the effects of 1 on the mitochondria, in particular on ROS levels, the alteration of the mitochondrial membrane potential, and the functioning of the respiratory chain. Treatment of MCF-7 cells with complex 1 induced a dose-and time-dependent increase in the cellular basal ROS production ( Fig.…”
mentioning
confidence: 99%